The Management of Phimosis Seen After Circumcision with Thermocautery - ÇAM, HAYDAR KAMİL (UROL & NEPHROL RES CTR-UNRC, 2020)
Objective: One of the most frequent complications after circumcision by thermocautery is phimosis. In this study, we aimed to present the functional and cosmetic results of the modified sleeve technique for the correction of this iatrogenic phimosis. Materials and Methods: The study group included iatrogenic phimosis cases who underwent circumcision using thermocautery during the last eight years. Initially, steroid creams were applied on these patients for six weeks. Patients who did not respond to this treatment underwent surgery using the modified sleeve technique. Control visits were performed at the first and fourth postoperative weeks. Results: A total of 32 patients with a median age of 5.1 +/- 1.1 years were included in the study out of 13285 circumcisions by thermocautery. No positive treatment outcomes were obtained by topical steroids, and all patients proceeded to surgery by modified sleeve technique. Median operative time was 25 +/- 2.3 minutes. Cosmetic and functional outcomes were satisfactory in all cases. Conclusion: There is no place for topical steroids in management of iatrogenic phimosis after thermocautery is observed, thus, early surgery is advised to avoid emotional stress. Our modified sleeve technique can achieve maximum cosmetic and functional outcomes without leading to extreme shortening of the penile skin and mucosa.
Keywords: cautery; circumcision; modified sleeve; phimosis